Application of Vegetable Insecticides from (Cymbopogon nardus L. Rendle) Extract Against Major Pests of (Capsicum frutescens L.) in Uuwan Village - Maningkas, Praise Frena; Pinaria, Betsy Agustina Naomi; Lengkong, Maxi (Sam Ratulangi University, 2024)
This research aims to control insect pests found on chili plants (C. frustescens L.) using the botanical insecticide lemongrass extract (Cymbopogon nardus) which is environmentally friendly and easy to apply by farmers in the field. The design used in this research was a randomized block design consisting of 5 treatments with 4 replications. The 5 treatments include: S0 as a control, S1 spraying once a week, S2 spraying once every 2 weeks, S3 spraying once every 3 weeks, and S4 spraying once every 4 weeks. Each experimental plot consisted of 30 chili plants. The research results found 4 types of pests on chili plants, namely, A. gossypi, B. tabaci, S. Litura, and M. Persicae. Compounds in citronella extract can repel or inhibit the growth of pests on Capsicum frutescens. The 2-week interval of spraying vegetable pesticide with Cymbopogon nardus extract has a significant effect on the pests Bemisia tabaci, Aphis gossypi and Myzus persicae. Keywords: Vegetable insecticide, Capsicum frustescent, Cymbopogon nardus, major pests Abstrak Penelitian ini bertujuan untuk mengendalikan hama serangga yang terdapat pada tanaman cabai (C. frustescens L.) menggunakan insektisida nabati Ekstrak Serai Wangi (Cymbopogon nardus) yang ramah terhadap lingkungan dan mudah diterapkan oleh petani di lapangan. Rancangan yang digunakan pada penelitian ini adalah rancangan acak kelompok yang terdiri dari 5 perlakuan dengan 4 kali ulangan. 5 perlakuan diantaranya : S0 sebagai control, S1 penyemprotan dilakukan 1 kali seminggu, S2 penyemprotan dilakukan 2 minggu 1 kali, S3 penyemprotan dilakukan 3 minggu 1 kali dan S4 penyemprotan dilakukan 4 minggu 1 kali. Setiap plot percobaan terdiri dari 30 tanaman cabai. Hasil penelitian ditemukan 4 jenis hama pada tanaman cabai yaitu, A. gossypi, B. tabaci, S. Litura dan M. Persicae. Senyawa pada ekstrak serai wangi dapat menolak atau menghambat pertumbuhan hama pada tanaman Capsicum frutescens. Interval waktu tiap 2 minggu penyemprotan pestisida nabati ekstrak Cymbopogon nardus berpengaruh nyata terhadap hama Bemisia tabaci, Aphis gossypi dan Myzus persicae. Kata Kunci: Insektisida nabati, Capsicum frustescens, Cymbopogon nardus, Hama utama